Classical Novae as Supersoft X-ray Sources in the Andromeda Galaxy - Henze, Martin; Pietsch, Wolfgang; Haberl, Frank; Hernanz, Margarita; Sala, Gloria; Della Valle, Massimo; Hatzidimitriou, Despina; Rau, Arne; Hartmann, Dieter H.; Burwitz, Vadim; Greiner, Jochen (Binary Paths to Type Ia Supernovae Explosions, 2013)
We review the first results of a dedicated, on-going monitoring project for supersoft X-ray source (SSS) states of classical novae (CNe) in the central region of the Andromeda galaxy (M 31). So far, during three high-cadence observation campaigns with the X-ray telescopes XMM-Newton and Chandra from 2006 until 2009 we detected 21 CNe, only four of which were seen in X-rays before. This increased the total number of known CNe with X-ray counterparts in M 31 to 60, which is significantly larger than for any other galaxy, including the Milky Way. We compiled a catalog of X-ray and optical properties for these 60 sources which allowed us to perform source statistics and population studies of CNe with SSS state in M 31 for the first time. Here we review the results of this analysis: (i) several correlations between X-ray and optical parameters, (ii) an analysis of the intrinsic fraction of CNe with SSS state, and (iii) the first nova population study in X-rays. Our first results are promising, however a continuing monitoring of the unique target M 31 is strongly needed to extend this valuable data base and to refine the early statements and predictions.
Keywords: CATACLYSMIC VARIABLES; galaxies: individual (M 31); Novae; X-rays: binaries